STUDENTS’ PERSPECTIVES OF PADLET APPLICATION AS EDUCATIONAL TOOL IN EFL WRITING CLASSROOM - Muhammad Rony; Farida Hamid; Atik Yuliyani; Nuraeni Nuraeni (Universitas Negeri Islam Sumatera Utara, 2024)
Today, almost every level of education makes use of digital technologies such as mobile devices and applications. It is intended to improve students' classroom experience and performance by providing a fun and interesting learning environment. Among these applications is Padlet. It allows Students and teachers can post pictures, audio, videos, and assignments on its virtual wall. The purpose of this research is to find out what students think about the Padlet application in the EFL writing classroom. Purposive sampling was used to select 82 participants from twelfth-grade senior high school students. This study used a qualitative method with a case study approach to investigate in-depth information about students' perspectives. The instruments for this study were a closed-ended questionnaire and semi-structured interviews. According to the data gathered from the questionnaires and interviews, the students in their writing class have positive attitudes toward Padlet. Padlet provides students with a fun and interesting learning environment while also improving their motivation, collaboration, language development, and lowering their learning anxiety. However, when using Padlet, two factors must be considered: a lack of interaction between teacher and students, and an unstable internet connection. Overall, Padlet contributes significantly as a tool in the EFL writing classroom.